Emotional Experience and Conative Loyalty: The Mediating Role of Revisit Intention - Selfi Laela Sari; Burhanudin Burhanudin (Jurnal Manajemen dan Kewirausahaan, 2023)
This purpose of this study is to empirically investigate the influence of emotional experience and intention to revisit on conative loyalty, as well as the role of intention to revisit as a mediator between emotional experience and conative loyalty. The population of this research was the visitors of Sunan Ampel religious tourism, Surabaya, Indonesia. The data was analyzed using structural equation modeling. There were 267 respondents participated in this study. The findings show emotional experience has positive influences on both visitors’ conative loyalty and intention to revisit. Moreover, emotional experience influences conative loyalty through the mediation of revisit intention. The stronger the positive emotional experience perceived by visitors, the stronger their desire to return to the same location.